1992
DOI: 10.1104/pp.99.4.1469
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Vegetative Nitrogen Compositional Changes in Response to Reduced Reproductive Sink Strength

Abstract: N redistribution patterns and the N composition of vegetative tissues above the peduncle node of wheat (Triticum aestivum L.) plants with altered reproductive sink strength were evaluated to determine the role of vegetative storage proteins in the temporary storage of excess N destined for export. The degree of leaf senescence symptoms (loss of chlorophyll, total N, and ribulose-1,5-bisphosphate carboxylase/oxygenase) were quirements for N export or gene expression of VSP for the temporary storage of excess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…In contrast to Leguminosae, in Gramineae, special polypeptides like VSP were not detected in leaves and stems by the sink cut treatment. MacKown et al (1992) also reported that the special polypeptide was not detected in the flag leaf blade, flag leaf sheath and peduncle by the sink cut treatment in wheat.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to Leguminosae, in Gramineae, special polypeptides like VSP were not detected in leaves and stems by the sink cut treatment. MacKown et al (1992) also reported that the special polypeptide was not detected in the flag leaf blade, flag leaf sheath and peduncle by the sink cut treatment in wheat.…”
Section: Discussionmentioning
confidence: 94%
“…It seems that more efficient integration of nitrogen into plant metabolism (Hageman 1979), together with a more rapid N turnover (Cox et al. 1985, Van Sanford and Mackown 1987) characterized Toronto during phase 2, which not only allowed to respond to higher sink capacity for plant‐available N (Mackown et al. 1992, Pugnaire and Chapin 1992) but at the same time to maintain higher levels of canopy N content.…”
Section: Discussionmentioning
confidence: 99%
“…Early degradation of DNA and proteins can be explained with the need of rdocating nutritional resources when the demand for nitrogen supply increases in the developing seeds (BARNEIX & GUITMAN, 1993). Other studies support the importance of the nitrogen translocation to the growing kernels (PEOPLES et al, 1980;MACKOWN et al, 1992;MARTIN DEL MOLINO et al, 1995). While nucleic acids and proreins are rapidly metabolised, the photosynthetic apparatus remains efficient as long as possible, because it can still provide an important source of nutrients.…”
Section: Discussionmentioning
confidence: 93%